Rainfall-runoff modeling of urban floods using GIS and HEC-HMS - Priyanka Sharad Jawale; A.D. Thube (MethodsX)
This research centres on simulating rainfall-runoff behaviour within the urban areas of Wakad Watershed in PCMC, Maharashtra, India, with a strong focus on improving water resource planning and availability assessments. Reliable forecasting of water availability is essential for sustainable water management, yet it often suffers from data limitations. To address this, the study employs advanced rainfall-runoff modelling techniques to offer accurate insights into the watershed’s hydrological processes, aiding data-driven decision-making. The watershed was meticulously delineated using a 7 m accuracy high-resolution Digital Elevation Model (DEM) coupled with 30 years of rainfall data from 1993 to 2023. GIS modelling in conjunction with HEC-HMS was carried out using the Soil Conservation Service Curve Number (SCS-CN), SCS Unit Hydrograph (SCS-UH), and Muskingum routing techniques. These approaches effectively integrated rainfall and watershed morphology details like slope, land use, soil properties, and climatic conditions. The model’s accuracy in predictions was enhanced through model calibration. The coefficient of determination (R2) exhibited 4.14 % increment improvement being raised from 0.67 to 0.699. NASH improved 44.23 % to a value of 0.624 displaying a competitive model. The Root Mean Square Error (RMSE) reduction of 51.90 % corroborated the effectiveness of the calibration made. RMSE fell from 1.235 to 0.813, while If PBIAS shifted from 43.69 % to 25.70 %. In summary, the model results indicate that the model demonstrates reasonable accuracy in representing the hydrological behaviour of the Wakad Watershed and provides a basis for developing water management plans in proactive environments of urban expansion. • Possessing highly detailed (7 m) DEM, as well as long term (30 years) precipitation data, allowed high-accuracy flood modelling alongside precise watershed characterization for the Wakad Watershed. • The combined application of GIS with the HEC-HMS modelling system, including SCS-CN, SCS-UH, and Muskingum methods, served as a robust framework for simulating urban floods and managing infrastructural development in rapidly evolving regions such as Wakad, PCMC. • Model calibration led to more accurate simulations with the tuned model achieving 44.23 % more Nash-Sutcliffe Efficiency, 51.90 % less RMSE, 4.14 % increment in R2 and 41.2 % less Percent Bias while demonstrating effective simulation of rainfall-runoff processes.